Proceedings of the 5th SEA-DR (South East Asia Development Research) International Conference 2017 (SEADRIC 2017) 2017
DOI: 10.2991/seadric-17.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between Students Critical Thinking Skill Using Problem Based Learning and Think Pairs Share on Coordination System Material

Abstract: Abstract-Global development requires education to always empower higher order thinking skills (HOTs). These skills are a sign that somebody has learned and thought to compete globally. Therefore, education has a pertinent role in preparing qualified human resources. In line with this, the teaching of biology has a potential to empower these HOTs, one of which is critical thinking skill. The purpose of this study was to determine the differences of students' critical thinking skill between students who were tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this regard, there were no previous reports that examine the effect of these two learning models on improving students' analytical thinking. However, the application of PBL has been reported to be able to improve critical thinking skills (Masek &Yamin, 2011;Nazir & Zabit, 2010;Ramdiah, 2017) and student problem-solving skills (Jonassen, 2011;Kadir, Abdullah, Anthony, Salleh, & Kamarulzaman, 2016). Furthermore, the application of TPS was also reported to be able to empower students' thinking skills (Ngozi, 2009), although the frequency was not as much as PBL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, there were no previous reports that examine the effect of these two learning models on improving students' analytical thinking. However, the application of PBL has been reported to be able to improve critical thinking skills (Masek &Yamin, 2011;Nazir & Zabit, 2010;Ramdiah, 2017) and student problem-solving skills (Jonassen, 2011;Kadir, Abdullah, Anthony, Salleh, & Kamarulzaman, 2016). Furthermore, the application of TPS was also reported to be able to empower students' thinking skills (Ngozi, 2009), although the frequency was not as much as PBL.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, Think Pair Share (TPS) and Problem based Learning (PBL) are two examples of cooperative learning that are often assessed for their benefits in learning. Previous research has reported the benefits of applying TPS to a variety of student thinking skills (Ngozi, 2009), while several other reports also address the benefits of applying PBL to various competencies (Bertacchini De Oliveira et al, 2016;Ramdiah, 2017;Sastrawati, Rusdi, &Syamsurizal, 2011;Talat & Chaudhry, 2014;Yaqinuddin, 2013). However, studies that examine the effect of applying TPS or PBL on students' analytic abilities are still difficult to find, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%